Actors and agency in global social governance - Kaasch, Alexandra, 1977-; Martens, Kerstin (New York : Oxford University Press, 2015)
This volume provides a coherent and comprehensive account of the diverse actors and agencies involved in global social governance and seeks to advance our understanding of the global dimension of social policy.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on October 14, 2015).
Keywords: Social policy; Social policy -- International cooperation; Globalization